Case Report: Bilateral targeted intraoperative radiotherapy: a safe and effective alternative for synchronous bilateral breast cancer - Bhimani, Fardeen; McEvoy, Maureen; Gupta, Anjuli; Pastoriza, Jessica; Shihabi, Areej; Basavatia, Amar; Tomé, Wolfgang A.; Fox, Jana; Mehta, Keyur; Feldman, Sheldon (Frontiers in Oncology, 2023)
The incidence of bilateral breast cancer (BBC) ranges from 1.4% to 11.8%. BBC irradiation is a challenge in current clinical practice due to the large target volume that must be irradiated while minimizing the dose to critical organs. Supine or prone breast techniques can be used, with the latter providing better organ sparing; both, however, result in lengthy treatment times. The use of Intra-operative radiotherapy (IORT) in breast cancer patients who choose breast conservation has been highlighted in previous studies, but there is a scarcity of literature analyzing the utility and applicability of IORT in BBC. This case series aims to highlight the applicability of administering bilateral IORT in patients with BBC.Case Reports: Five patients with bilateral early-stage breast cancer (or DCIS) were treated with breast-conserving surgery followed by bilateral IORT. Of the 10 breast cancers, 8 were diagnosed as either DCIS or IDC, while the other 2 were diagnosed as invasive lobular carcinoma and invasive carcinoma, respectively. During surgery, all patients received bilateral IORT. Furthermore, 1 patient received external beam radiation therapy after her final pathology revealed grade 3 DCIS. The IORT procedure was well tolerated by all five patients, and all patients received aromatase inhibitors as adjuvant therapy. Additionally, none of these patients showed evidence of disease after a 36-month median follow-up.Our findings demonstrate the successful use of IORT for BCS in patients with BBC. Furthermore, none of the patients in our study experienced any complications, suggesting the feasibility of the use of IORT in BBC. Considering the benefits of improved patient compliance and a reduced number of multiple visits, IORT may serve as an excellent patientcentered alternative for BBC. Future studies are recommended to reinforce the applicability of IORT in patients with BBC.